The diurnal cycle and event-scale precipitation characteristics in Galápagos at different altitudes during ENSO 2022-2024 - Tenelanda, Pablo; Turini, Nazli; Orellana-Alvear, Johanna; Delgado Maldonado, Byron; Bendix, Jörg; Célleri, Rolando (ERDKUNDE, 2025)
An understanding of sub-hourly precipitation variability in the Galapagos Islands is crucial for water resource management and effective biodiversity conservation. This study compares the diurnal cycle and event-scale precipitation characteristics (ESPC), such as mean and maximum intensity, duration and rainfall accumulation at different altitudes during El Niño-Southern Oscillation (ENSO) 2022-2024 on Santa Cruz Island. The La Niña phase was analyzed from April 2022 to January 2023 and the El Niño phase from June 2023 to April 2024. Precipitation data, recorded every 10 minutes, was collected from a recently established network of automatic weather stations, which were strategically positioned at three windward and two leeward sites. The results suggest that the diurnal cycle was influenced by altitude, with a maximum variability between morning and afternoon, regardless of ENSO phase. During La Niña, ESPC exhibited similarities at intermediate altitudes at both windward and leeward sides. However, rainfall events at the island’s summit were less intense and of longer duration. During El Niño, the highest intensities were observed along the coast and at intermediate altitudes of both windward and leeward locations. In contrast, at the top of the island, rainfall events were less intense and more prolonged. At all altitudes, more than half of the rainfall events corresponded to garúa events, and at the top of the island, almost all events were of this type. At this altitude, the contribution of garúa events to the total rainfall accumulation was 80% and 85% for La Niña and El Niño, respectively. This study provides a detailed analysis of how sub-hourly precipitation varies significantly at different altitudes on the windward and leeward sides as a function of ENSO phases, providing valuable baseline information for future studies in this unique and fragile ecosystem.